The Jacobean radical picture of The White Devil - González Fernández de Sevilla, José Manuel (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1996)
The White Devil presents a radical vision of Jacobean times. The play becomes a dramatic reflection of the crisis which brought about a new consciousness of life and death. Thus, it challenges an old order in need of change since everything is corrupted and abused. Characters are forced to live in a world of chaos and nonsense where ambiguity and appearances are the strategies to follow. Vittoria and Monticelso know how to use them to get power and social promotion. In this way drama shows a metatheatrical potential, for it contributes to give new solutions and to shape new expectations.